Pengaruh Komitmen Organisasi Terhadap Kinerja Karyawan di PT. Senyum Sehat Sejahtera - Destrina Permata Sari; Waloyo Waloyo; Komarun Zaman (Universitas Maritim AMNI Semarang, 2023)
This study to determine the effect of organizational commitment on employee performance at PT. Senyum Sehat Sejahtera. This study uses quantitative research with an descriptive approach. In this study saturated sampling was used as a sampling technique, as many as 20 employees at the company as samples in this study. Data collection techniques were in the form of observation and questionnaires. The results of this study indicate that Organizational Commitment (X1) has a partially positive and significant effect on Employee Performance.